2011
DOI: 10.1002/pd.2835
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐free fetal DNA testing: a pilot study of obstetric healthcare provider attitudes toward clinical implementation

Abstract: Objective To provide a preliminary assessment of obstetric healthcare provider opinions surrounding implementation of cell-free fetal DNA testing. Methods A 37-question pilot survey was used to address questions around the translation and use of non-invasive prenatal testing using cell-free fetal DNA. The survey was distributed and collected at a Continuing Medical Education course on obstetrics and gynecology. Results Of 62 survey respondents, 73% are female and 87% hold MD/DO degrees. Respondents general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 24 publications
(28 reference statements)
3
66
1
Order By: Relevance
“…The survey was grounded in concepts and questions posed in the literature and through previous empirical research conducted by our team (Sayres, Allyse, Norton, & Cho, 2011). A broader team of bioethics scholars reviewed this survey for readability and content.…”
Section: Methodsmentioning
confidence: 99%
“…The survey was grounded in concepts and questions posed in the literature and through previous empirical research conducted by our team (Sayres, Allyse, Norton, & Cho, 2011). A broader team of bioethics scholars reviewed this survey for readability and content.…”
Section: Methodsmentioning
confidence: 99%
“…Before implementation, it is important to evaluate service user views and preferences to ensure that when the test is introduced the needs of all stakeholders are met. So far, a small number of studies evaluating stakeholder views of NIPT for Down's syndrome have been conducted [15,16,17,18,19]. However, no previous qualitative studies have examined the opinions of pregnant women with a range of different experience of Down's syndrome screening and diagnosis in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…Implementation into state funded healthcare systems requires further information to determine where it fits in the care pathway, what the uptake might be in clinical practice, whether the rate of invasive testing will change and if so how this might impact on service provision and training, the costs for the public health service and for service users, and how best to educate women and health professionals to ensure that informed choice is maintained. There is information available to address some of these issues, but it is largely based on studies assessing patient and health care views based on hypothetical scenarios in which indications are that uptake will be high (Sayres et al 2011;Tischler et al 2011;Hill et al 2012a;Lewis et al 2013Lewis et al , 2014a or modeled data to inform discussions on potential economic impact Beulen et al 2014;Morris et al 2014). However, it is well documented that what happens in clinical practice does not always reflect what people say/believe they will do hypothetically.…”
Section: Implementation Of Nipt For Aneuploidy Into Public Sector Heamentioning
confidence: 99%
“…Evaluation in clinical practice, albeit as part of a trial , is showing that a small but significant proportion of women with a very high-risk (.1:30) or an ultrasound abnormality are being advised to opt for invasive testing, and that some of the women in the lower risk category (1:150-1: 1000) are content with their risk and decline NIPT (LS Chitty, unpubl.). One other factor influencing health economic aspects is that studies based on hypothetical scenarios of offering NIPT have indicated that an additional group of women, who would decline current screening and diagnosis because of the risk of miscarriage, will undergo NIPT to plan and prepare for the birth of an affected child (Sayres et al 2011). Both uptake and clinical utility will clearly influence the economic aspects of implementation.…”
Section: Economic Aspectsmentioning
confidence: 99%
See 1 more Smart Citation